Heterogeneous nuclear ribonucleoprotein K is overexpressed in acute myeloid leukemia and causes myeloproliferation in mice via altered Runx1 splicing. Issue 4 (9th December 2022) - Aitken, Marisa J L; Malaney, Prerna; Zhang, Xiaorui; Herbrich, Shelley M; Chan, Lauren; Benitez, Oscar; Rodriguez, Ashley G; Ma, Huaxian; Jacamo, Rodrigo; Duan, Ruizhi; Link, Todd M; Kornblau, Steven M; et al.
Abstract: Acute myeloid leukemia (AML) is driven by numerous molecular events that contribute to disease progression. Herein, we identify hnRNP K overexpression as a recurrent abnormality in AML that negatively correlates with patient survival. Overexpression of hnRNP K in murine fetal liver cells results in altered self-renewal and differentiation potential. Further, murine transplantation models reveal that hnRNP K overexpression results in myeloproliferation in vivo . Mechanistic studies expose a direct functional relationship between hnRNP K and RUNX1 —a master transcriptional regulator of hematopoiesis often dysregulated in leukemia. Molecular analyses show that overexpression of hnRNP K results in an enrichment of an alternatively spliced isoform of RUNX1 lacking exon 4. Our work establishes hnRNP K's oncogenic potential in influencing myelogenesis through its regulation of RUNX1 splicing and subsequent transcriptional activity.